2019
DOI: 10.1177/2192568219880822
|View full text |Cite
|
Sign up to set email alerts
|

Does Size Matter? An Analysis of the Effect of Lumbar Disc Herniation Size on the Success of Nonoperative Treatment

Abstract: Study Design: Retrospective study. Objective: In this study, we examined whether the size of a lumbar disc herniation (LDH) is predictive of the need for surgical intervention within 2 years after obtaining an initial magnetic resonance imaging (MRI) scan. We hypothesized that a fragment that occupied a larger percentage of the spinal canal would not predict which patients failed conservative management. Methods: Using the ICD-10 code M51.26, we identified patients at a single academic institution, across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…One prior study which examined 2.5 million adults in the USA with low back and/or lower extremity pain and no red flag diagnosis found that 1.2% of patients underwent surgery over a 1-year follow-up period 60. While smaller studies have reported a higher frequency of discectomy of 5% or greater,44 61–63 our study had a relatively young population and several exclusions, which could explain the frequency of discectomy being on the lower end of the range of prior studies. Further, most discectomies occurred in the first year of follow-up in our study, with only a small increase during the 2-year follow-up window.…”
Section: Discussionmentioning
confidence: 69%
“…One prior study which examined 2.5 million adults in the USA with low back and/or lower extremity pain and no red flag diagnosis found that 1.2% of patients underwent surgery over a 1-year follow-up period 60. While smaller studies have reported a higher frequency of discectomy of 5% or greater,44 61–63 our study had a relatively young population and several exclusions, which could explain the frequency of discectomy being on the lower end of the range of prior studies. Further, most discectomies occurred in the first year of follow-up in our study, with only a small increase during the 2-year follow-up window.…”
Section: Discussionmentioning
confidence: 69%
“…Generally speaking, the probability of surgery is greater when the herniated disc is larger. However, recently Gupta et al pointed out that it is not feasible to use the size of the intervertebral disc herniation (as a percentage of the spinal canal area) to predict whether surgery is required after 6 weeks of conservative treatment [ 14 , 15 ]. Similarly, cases of reabsorption of large herniated discs have been reported many times [ 14 , 16 , 17 ].…”
Section: Clinical and Imaging Features Of Ldh Prone To Reabsorptionmentioning
confidence: 99%
“…Overall, there is currently not unequivocal evidence to suggest that operating on a DPP dog is urgent although, on the other hand, there is no suggestion that it is detrimental either—simply strong evidence that it is not warranted in ALL patients. There is also plentiful evidence from human and canine studies that cord compression associated with a herniated disc can, at least in some cases, disappear without medical intervention ( 28 , 37 , 41 43 ). Anecdotally we know that some cases appear to respond rapidly to surgical decompression, whereas many do not.…”
Section: Timing Of Surgerymentioning
confidence: 99%